Telecommunications policy in the European Union: developing the information superhighway. - CURWEN, Peter (1995)
Notes that there is considerable variation in the provision of telecommunications services between the member states of the European Union, and the main bodies of the EU - Commission, Council and Parliament - have become heavily involved in the process of restructuring the telecommunications sector. Analyses what has happened so far, is happening and is likely to happen as the Union seeks to impose its authority upon often recalcitrant member states.